Analisis Kestabilan Lereng Untuk Perencanaan Optimalisasi Penambangan Pada Lokasi Tambang Air Laya (TAL) Barat PT. Bukit Asam Tbk - Aprilian Susanto; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract PT. Bukit Asam Tbk is one of the largest coal mining companies in Indonesia which has several mining locations, one of which is the Air Laya Barat Mine. Currently, the depth of the Air Laya Barat Mine is -57 m in section A-A '. In order for coal production to increase in the next quarter, the TAL Barat pit mining plan will optimize to a depth of -80 m because there is still coal that allows it to be mined. In the optimization plan, important things that need to be analyzed, one of which is the slope safety factor, the method used in this research is the bishop method. As a result of the research the conclusions are as follows. First, the weight of OB (γ) = 20.07kN / m3, cohesion (c ') = 25.20 kPa and the inner angle of shear ((') = 41,63°. Weight of Lower C (γ) = 23.52 kN / m3, cohesion (c ') = 22.55 kN / m2 and inner shear angle (ϕ') = 40,59 °. Second, for modeling using the Geostudio Slope / W 2012 program with FK Overall Slope is 2,788. So that the stability of the slope against the optimization plan from a depth of -57 m to a depth of -80 m is still safe to continue